Video Game Training Enhances Visuospatial Working Memory and Episodic Memory in Older Adults - Toril, Pilar; Reales, José M.; Mayas, Julia; Ballesteros, Soledad (Frontiers in Human Neuroscience, 2016)
In this longitudinal intervention study with experimental and control groups, we investigated the effects of video game training on the visuospatial working memory and episodic memory of healthy older adults. Participants were 19 volunteer older adults, who received 15 1-hr video game training sessions with a series of video games selected from a commercial package (Lumosity), and a control group of 20 healthy older adults. The results showed that the performance of the trainees improved significantly in all the practiced video games. Most importantly, we found significant enhancements after training in the trained group and no change in the control group in two computerized tasks designed to assess visuospatial working memory, namely the Corsi blocks task and the Jigsaw puzzle task. The episodic memory and short-term memory of the trainees also improved. Gains in some working memory and episodic memory tasks were maintained during a 3-month follow-up period. These results suggest that the aging brain still retains some degree of plasticity, and that video game training might be an effective intervention tool to improve working memory and other cognitive functions in older adults.